From Writing to Philosophizing: A Lesson from Platonic Hermeneutics for the Methodology of the History of Philosophy - Vasilakis, Dimitrios (Conatus - Journal of Philosophy, 2020)
In this paper, I try to exploit some lessons drawn from reading Plato in order to comment on the methodological ‘meta-level’ regarding the relation between philosophizing and writing. After all, it is due to the medium of written word that we come to know past philosophers. I do this on the occasion of the ostensible conclusion in Plato’s Meno. This example illuminates the ‘double-dialogue’ hermeneutics of Plato and helps to differentiate Plato’s dialogues from dialogical works written by other philosophers, such as Berkeley. As a result, it becomes clear that, like with Plato’s case, a historian of philosophy must not only have a philosophical training, but also a subtle philological background, when attempting to come into dialogue with dead philosophers.